The influence of different lighting sources on growth and development of tomato plants; IOP Conference Series: Materials Science and Engineering; Vol. 510 : High Technology: Research and Applications (HTRA-2018) - Yamburov M. S. Mikhail; Romanova S. B. Svetlana; Smolina V. M. Valentina; Burenina A. A. Anastasia; Astafurova T. P. Tatyana; Turanov S. B. Sergey Borisovich; Romanenko S. A. Sofia (2019, 2019)
Title screen